Wilson disease diagnosed incidentally by targeted gene panel sequencing in a Korean boy with severe obesity - Minji Im; Ari Song; Jiyeon Kim; Min-Sun Kim; Sae-Mi Lee; Mi Jin Kim; Sung Yoon Cho; Dong-Kyu Jin (Korean Society of Pediatric Endocrinology, 2022)
Wilson disease (WD) is a relatively common genetic hepatic disease in children and is characterized by excessive copper accumulation, predominantly in the liver and brain. It is an autosomal recessive disease caused by an ATP7B mutation that causes brain degeneration and is potentially fatal if diagnosed late or untreated. In the early phase of WD, its initial presentation may include mild hepatic involvement. WD may be overlooked as a cause of liver disease due to severe obesity but should not be excluded from differential diagnosis. We report a case of WD with severe obesity and fatty liver diagnosed in the early phase by targeted gene panel sequencing and review the endocrine problems associated with WD. Early suspicion of WD is important for good prognosis.